The Strange Case of Tough White Seabream (Diplodus sargus, Teleostei: Sparidae): A First Approach to the Extent of the Phenomenon in the Mediterranean - Casadevall, Margarida; Rodríguez-Prieto, Conxi; Pueyo, Josep; Martí, Carolina; Merciai, Roberto; Verlaque, Marc; Real, Enric; Torres, Jordi; Richir, Jonathan (Frontiers in Marine Science, 2020)
A worrying phenomenon has been affecting the common white seabream (Diplodus sargus) for near 40 years. Professional and recreational fishers from the Mediterranean coasts and the Atlantic coasts of Europe and Macaronesia have reported individuals of white seabream that became "like a tire" after cooking, and consequently inedible. The phenomenon was related neither to the freshness of the fish nor to the way it had been preserved or cooked. According to recreational fishers, this abnormally tough specimens (ATS) phenomenon appeared singularly in time, in different places and to different extents. This singular, scattered appearance, with no area of origin from which to spread, de facto excluded any process of contagion. In order to compensate for the lack of knowledge and understanding related to this issue, we undertook a first study aimed at addressing the extent of the white seabream anomaly in the western Mediterranean. To reach this objective, we carried out surveys on voluntary basis among fishers (both professional and recreational) and researchers throughout the western Mediterranean. Data from the surveys (n = 270) were then analysed to evaluate the distribution of ATS and its possible relationship with human activities. Results showed that the anomaly affected the white seabream and very occasionally some other species, mainly of the same family Sparidae. In addition, the phenomenon did not occur simultaneously in the different areas surveyed over the last years and in some places it seems to have disappeared. We highlighted a possible link between ATS occurrence and the presence of human activities in adjacent areas. We hypothesized pollution - including copper - could be a possible driver of ATS. Results suggest a tendency of ATS to cluster around fish farms and commercial and industrial ports, although we are aware other human factors might also influence the phenomenon. To conclude, the present study gives an overview of the importance of the white seabream anomaly in the Mediterranean and encourages further research to disentangle the exact mechanisms behind this phenomenon.